1988
DOI: 10.3354/meps049001
|View full text |Cite
|
Sign up to set email alerts
|

Seabird foraging tactics and water clarity are plunge divers really in the clear?

Abstract: A steep turbidity gradient across 3 shelf water masses and the Gulf Stream on the upper conhnental slope off the coast of the southeastern USA formed the basis for testing relationships between predator foragng tactics and relative detectability of prey. Censuses of seabirds were used to test a hypothesis originally proposed by Ainley (1977): plunge diving (plummeting from the air to subsequently capture prey underwater using the momentum of the fall) is more prevalent in clear as opposed to turbid surface wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 17 publications
(24 reference statements)
3
32
0
Order By: Relevance
“…The distribution of piscivorous waterbirds should be affected by water clarity due to its impact on prey accessibility (Abrahams and Kattenfeld 1997). Henkel (2006) found that visual pursuit waterbirds such as cormorants favor clear waters due to increased visual acuity, whereas shallow plunge diving piscivores such as terns favor more turbid conditions (Hanley and Stone 1988). Cormorants in the WLC followed the expected trend of being more abundant in the less turbid estuaries, and Common Tern more plentiful on the relatively turbid lakes.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of piscivorous waterbirds should be affected by water clarity due to its impact on prey accessibility (Abrahams and Kattenfeld 1997). Henkel (2006) found that visual pursuit waterbirds such as cormorants favor clear waters due to increased visual acuity, whereas shallow plunge diving piscivores such as terns favor more turbid conditions (Hanley and Stone 1988). Cormorants in the WLC followed the expected trend of being more abundant in the less turbid estuaries, and Common Tern more plentiful on the relatively turbid lakes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Day et al (2003) found that foraging areas of closely related and sympatrically occurring marbled (Brachyramphus marmoratus) and Kittlitz's (B. brevirostris) murrelets differed mainly in water clarity. Plungedivers, such as terns, might benefit from feeding over turbid water, because the small fishes that constitute their prey move closer to the well-lit surface waters, where in turn, the phytoplankton tends to concentrate (Haney and Stone 1988;Baptist and Leopold 2010). The contrast degradation theory predicts that high turbidity not only decreases the visibility of objects, but also increases the minimum size of particles that can be detected (Lythgoe 1979;De Robertis et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Mew gulls were considered piscivores because they were observed in mixed-species foraging flocks where salmon fry were abundant. Marbled murrelets and both mergansers are pursuit divers (Table 1; observed in this study), which remain submerged for sustained periods and may emerge some distance from where they entered the water (Haney & Stone 1988). We could not directly observe predation on salmon fry by pursuit divers; however, they were observed in mixed-species foraging flocks near concentrations of fry and are known to consume juvenile (Table 1) We therefore considered them to be piscivores for the purposes of this study.…”
Section: Methodsmentioning
confidence: 66%